Geological storage of carbon dioxide - Baines, Shelagh J.; Worden, Richard H. (Geological Society special publication, 2004)
Carbon dioxide (CO 2) is the main compound identified as affecting the stability of the Earth's climate. A significant reduction in the volume of greenhouse gas emissions to the atmosphere is a key mechanism for mitigating climate change. Geological storage of CO 2, or the injection and long-term stabilization of large volumes of CO 2 in the subsurface in saline aquifers, in existing hydrocarbon reservoirs or in unmineable coal seams, is one of the more technologically advanced options available. A number of studies have been carried out and are reported here.